Early childhood education : values and practices in Denmark - Hygum, Erik, ....-; Moller Pedersen, Peter, ....-; Jensen, Jens-Ole, ....-; Ostergaard Andersen, Peter, ....-; Buus, Anne Mette, ....- (Aarhus : Viasytime, 2014)
The aim of this book is to highlight the basic pedagogical knowledge and values in Danish educational daycare institutions (kindergartens). In the book we present a selection of current research and development projects covering central issues of the pedagogical work in Danish early childhood education. We present the knowledge, experience and values from the early childhood education tradition in Denmark to an international audience. The articles are written by researchers and educators from the Professional Bachelor Program of pedagogues at university colleges' in Denmark and by researchers from Danish universities. Read about Child-centered pedagogy, Professional bachelor degree of pedagogues, Child-care in a welfare state, Creativity in childcare, Forms of knowledge in pedagogical work, Inclusion as an objective, Outdoor play and learning, Health and pedagogical practice, Social pedagogy, Mediaplay, Language development, Danish pedagogy in international perspective.
Keywords: Kleuteronderwijs -- Denemarken